Resistance and Reliance of Dalit Women in India: A Study on Three Generation of Indian Dalit Women Writer - J, JenithaBlessy.; Bhuvaneswari, V. (International Journal of Psychosocial Rehabilitation, 2020)
It is important to note that untouchability is one of the greatest evils in India. The country has been facing the from the time immemorial. Dalit women are considered to be the most deprived because they suffered tripartite marginalisation. As Maya Pandit observes that Dalit women writers have negotiated a long progression over the last four decades and their consciousness of what it means to be a Dalit woman in India has evolved in many ways the present study aims to explore the distressing effects caused by the caste-based social system on Dalit women from the past few epochs through the lens of Dalit women writers. Their writings reflect a decade of active intervention in Dalit literary discourse in India that engendered a new vibrant voice that interrogated literary and cultural stereotypes by setting up new yardsticks and forging fresh perspectives on literary paradigms. The paper further aims at exploring the dynamic intersection between gender and caste in the works of Dalit women writers by tracing the difference between the Dalit women writers and their counterparts.